Disentangling tree species identity and richness effects on the herb layer: first results from a German tree diversity experiment. (4th March 2015) - Ampoorter, Evy; Baeten, Lander; Vanhellemont, Margot; Bruelheide, Helge; Scherer‐Lorenzen, Michael; Baasch, Annett; Erfmeier, Alexandra; Hock, Maria; Verheyen, Kris; Michalet, Richard
Abstract Questions The forest herb layer provides a multitude of ecosystem services as a result of its species‐rich character. Herb layer diversity and biomass are both influenced by tree layer composition and species richness through species‐specific influences on environmental conditions. The results of observational studies on richness–biomass relationships between tree and herb layer have not been unequivocal. We examined tree species identity and richness effects on herb layer species richness, composition, biomass and nutrient concentrations in young experimental tree plantations. Location BIOTREE tree diversity experiment, Kaltenborn, Germany. Methods Sixteen plots were planted in 2004, using a pool of four tree species (beech, oak, Douglas‐fir, Norway spruce) and four richness levels, comprised of all possible species combinations. In this way, complete dilution was avoided, allowing separation of tree species identity and richness effects. Mixed plots consisted of a matrix of monospecific patches. One permanent vegetation quadrat of 1 m2 was established in the centre of four patches per plot. The herb layer was monitored in 2004 and 2010; in 2010 light measurements were performed in each quadrat, and in 2011 above‐ground biomass was sampled on 0.25 m2 within the quadrat. Results Community composition shifted markedly between 2004 and 2010. Tree species identity did not yet influence temporal compositional turnover or herb layer species richness in 2004 and 2010. Ellenberg N indicated a temporal shift towards lower soil fertility under all tree species, whereas Ellenberg R indicated decreasing soil acidity under beech and Douglas‐fir. Ellenberg L and F showed no shift from 2004 to 2010. Apart from the significantly lower Ellenberg N for beech, none of the Ellenberg indicators indicated interspecific differences. Douglas‐fir, and especially Norway spruce, negatively influenced total above‐ground herb layer biomass. Douglas‐fir also induced lower relative light availability, higher potassium, magnesium and nitrogen concentrations and lower carbon:nitrogen ratios in the total biomass. Higher tree species richness positively affected graminoid and total biomass and also slightly increased plot‐level herb layer species richness. Conclusions Despite the young age of the experiment, tree species identity and richness effects on the herb layer could be discerned. We expect these relations to become stronger with time.